Readiness of Work affected by Work Procrastination and Hedonic Lifestyle - R D Santy; P A Pratama (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study was to determine the effect of work procrastination and hedonic lifestyle toward readiness of work on one of the government office in Kab. Cianjur. The research method use is quantitative which contains a description of the condition of each variable with a reference to the calculation is a Likert Scale, as well as a qualitative method that contains the results of the relationship between independent variables to the dependent variable with a multiple linear regression analysis approach. The sampling technique used is the census technique, which is as many as 47 government employee in one of the government office in Kab. Cianjur. The result of the this study is that partially there is a significant negative effect between work procrastination and hedonic lifestyle toward readiness of work. The form that is most often carried out by that government employee of work procrastination is procrastination to start and finish the task. Meanwhile, the hedonic lifestyle is a consumption style. And for readiness of work that needs to be improved is in terms of skills. The impact of this study is to increase work productivity by change the unnecessary behavior work enviroment in particular at public service.